‘If they see you bleeding they will quarantine you’: Women’s help-seeking for violence during the Ebola and COVID-19 outbreaks in Sierra Leone - Rose Burns; Neha Singh; Maseray Fofanah; Tehsie Momoh; Shelley Lees; Janet Seeley; Manuela Colombini (Global Public Health)
There is increased awareness of the gendered impacts of outbreaks, including an exacerbation of violence against women and disruptions to essential health service delivery for women. However, there is limited understanding of women’s own experiences of deciding to use the health system after experiencing violence in settings affected by major emergent outbreaks like Ebola and COVID-19. Drawing on data from 37 in-depth interviews and 4 focus group discussions conducted in Sierra Leone we described survivors’ help-seeking pathways and interactions with the health system. Deciding to seek help and selecting a source of support was dependant on how ‘unacceptable’ the type of violence was, women’s needs (be they for physical, psychological or social trauma) and the risk versus benefit anticipated in accessing support. Informal providers such as local mediators were often the first place that survivors sought help. Pre-existing challenges around access and poor-quality service provision were exacerbated by the outbreaks. Fear of infection, quarantine and widespread distrust of the Ebola response shaped women’s help-seeking especially if symptoms like bleeding could resemble the virus. Our findings support the need to re-orientate towards survivor-defined interventions that are flexible in providing a wider range of support choices.